PORTRAYING EFL STUDENTS’ WRITING SELF EFFICACY ACROSS IDEATON, CONVENTION, AND SELF-REGULATION: A QUALITATIVE EXPLORATION - Eliza Trimadona; Urip Sulistiyo; Hadiyanto; Mukhlash Abrar (English Review: Journal of English Education, 2026)
Writing self-efficacy plays a crucial role in shaping EFL students’ engagement, strategic behavior, and confidence in academic writing. This qualitative study investigates how university EFL students construct their writing self-efficacy through three interrelated dimensions: ideation, convention, and self-regulation. Semi-structured interviews were conducted with undergraduate EFL students and analyzed using thematic analysis supported by NVivo. The findings reveal that students’ self-efficacy in ideation is strengthened by topic familiarity, the use of planning strategies, and access to external resources, enabling them to generate and organize ideas more confidently. In terms of convention, students’ confidence is closely associated with their perceived control over grammar, vocabulary, and mechanics, often supported by digital tools as mediational resources. Self-regulation emerges as a dynamic dimension, reflected in students’ ability to manage focus, set goals, and sustain motivation, although their efficacy frequently fluctuates due to reliance on external demands such as deadlines. The results indicate that writing self-efficacy is a multidimensional and context-dependent construct shaped by the interaction of cognitive, linguistic, and regulatory processes. These findings highlight the importance of integrating strategic instruction, linguistic support, and self-regulatory guidance to foster sustainable writing self-efficacy in EFL higher education contexts.